Optimum parameter setting for potting machine on inductance products - Nurul Muhayu Ashikin, Rukmi (2018)
This thesis is about the improvement of the existing process on potting machine for inductance products in an industrial company, Vacuumschmelze Sdn. Bhd., located in Pekan, Pahang. In order to achieve the objective which is to make an improvement on the potting process, a method for optimization is conducted to investigate the best parameter that should be used on the potting machine that depends on the model of inductance. The approach in this project is based on the design of experiment of Taguchi method to determine the setting of the process parameters due to its precision, low cost and low time consuming, systematic and easy to analyze the result. Orthogonal Arrays of Taguchi, the signal and noise ratio, the analysis of variance (ANOVA) are employed to find the optimum parameter levels of factors. The results obtained from the experiment in Taguchi technique is analyzed using statistical software, Minitab. Confirmation test with the optimum level obtained is carried out to investigate the effectiveness of the experiment conducted.